Pathogenesis, Clinical, Diagnosis, Treatment, and Complications are Acute Pancreatitis - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
Lecture on the current state of the problem of acute pancreatitis. The pathogenesis, clinical picture, diagnosis and principles of treatment of the disease are considered. Particular attention is paid to indications and contraindications for conservative and surgical treatment of pancreatic necrosis, depending on the stage and severity of the disease. It is emphasized that stopping the acute inflammatory process in the gland does not mean complete recovery and morphological restoration of the pancreas. As a rule, pancreatic necrosis leads to the development of chronic pancreatitis, therefore, after discharge from the hospital, patients are subject to long-term restorative treatment aimed at restoring tissue trophism and gland function.